Reforming schools into health promoting schools: perspective based on expert consensus from a European multistakeholder consultation - Makris, Konstantinos C.; Philippou, Christiana; Vasileiou, Constantina; Tornaritis, Michael J.; Michaelidou, Stella Canna; Hadjigeorgiou, Charalambos; Kyriacou, Marina; Santamouris, Matthaios; Grotto, Itamar; Bose-O'Reilly, Stephan; Breda, Joao; van den Hazel, Peter (My University, 2026)
Every school on this planet should aim to become a healthy school. This is the motto of the WHO/UNICEF health promoting school strategic agenda (HPS). To address gaps and needs of children's health and educational inequalities in schools, a qualitative study was set up to synthesize experts' views and insights on school health programs and the HPS strategy in Europe. This multi-stakeholder consultation took place during an international children's health workshop in Cyprus (October 2024). Data was collected through focus group interviews with ~ 30 experts engaged in a multistakeholder consultation between academics, governmental officials, teacher liaisons, and health professionals, including WHO experts and NGOs. The consultation identified the following themes: systemic limitations in funding and sustainability of health education/promotion programs, enhanced curriculum needs for health literacy, limitations in school physical environment, rise in behavioral risk factors among children and adolescents, and growing mental health needs. A consensus was reached regarding the prerequisites and recommendations towards improving both health and educational outcomes for children; the implementation of holistic methodological frameworks, such as that of the human exposome and its exposomics tools were collectively proposed to better deploy the HPS recommendations in the school community.
Keywords: Wellbeing; Children; Environmental health; Exposome; Health services; Schools